Tanglewreck - Winterson, Jeanette 1959- (New York Bloomsbury Children's Books Distributed to the trade by Holtzbrinck Publishers, 2006)
Eleven-year-old Silver sets out to find the Timekeeper--a clock that controls time--and to protect it from falling into the hands of two people who want to use the device for their own nefarious ends.
Keywords: Time -- Juvenile fiction; Time travel -- Juvenile fiction; Space and time -- Juvenile fiction; Clocks and watches -- Juvenile fiction; Time -- Fiction; Time travel -- Fiction; Space and time -- Fiction; Clocks and watches -- Fiction